2011
DOI: 10.1002/ejic.201100379
|View full text |Cite
|
Sign up to set email alerts
|

Atom Transfer Radical Reactions as a Tool for Olefin Functionalization – On the Way to Practical Applications

Abstract: Transition‐metal‐catalyzed atom transfer radical reactions of halogenated compounds with olefins constitute a versatile tool in organic synthesis within the area of C–C bond forming transformations. The inter‐ or intramolecular versions, atom transfer radical addition (ATRA) or cyclization (ATRC), respectively, lead to the atom‐economic, useful synthesis of compounds that can be further functionalized. This contribution summarizes the recent developments in this area in terms of catalyst design as well as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(55 citation statements)
references
References 122 publications
1
50
0
4
Order By: Relevance
“…These side reactions not only decrease the yield in the desired addition products but also induce the accumulation of Cu 2+ , affecting the Cu + /[Cu 2+ ] ratio and finally causing the reduction of the catalytic activity of the catalysts. [24] As for the ATRA of MTCA to St, similar results were obtained. This is also shown in Tables 1 and 2.…”
Section: Atra Of CCL 4 To Mma and Mtca To St Using Multidentate Aminesupporting
confidence: 89%
“…These side reactions not only decrease the yield in the desired addition products but also induce the accumulation of Cu 2+ , affecting the Cu + /[Cu 2+ ] ratio and finally causing the reduction of the catalytic activity of the catalysts. [24] As for the ATRA of MTCA to St, similar results were obtained. This is also shown in Tables 1 and 2.…”
Section: Atra Of CCL 4 To Mma and Mtca To St Using Multidentate Aminesupporting
confidence: 89%
“…Both processes originated from well-known Kharasch addition in which polyhalogenated compounds were added to alkenes via free-radical means (13,39,40). Recent studies have also indicated that TPMA is a superior complexing ligand in ATRA (13,33,40,(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54) and ATRP (49,(55)(56)(57)(58) that utilize reducing agents. The role of a reducing agent in both systems is to continuously regenerate the activator species (copper(I) complex) from the corresponding deactivator (copper(II) complex).…”
Section: Catalysis With Transition Metal Complexes Containing Tpma LImentioning
confidence: 97%
“…(Eckenhoff & Pintauer, 2010a;Pintauer, 2008Pintauer, , 2009Pintauer, , 2010. Therefore, transition metal catalyzed (TMC) ATRA became a broadly applicable synthetic tool (Clark, 2002;Curran, 1992;De Campo et al, 2000;Eckenhoff & Pintauer, 2010b;Gossage et al, 1998;Muñoz-Molina et al, 2011;Pintauer, 2010;Severin, 2006). Largely based on chemo-, regio-, and stereoselectivity, it is generally accepted that the mechanism of TMC ATRA involves free radical intermediates (Asscher & Vofsi, 1961;Minisci, 1975).…”
Section: Historical Perspectivementioning
confidence: 99%